PENGARUH THE URGENT REHABILITATION PROJECT OF TANJUNG PRIOK TERHADAP PRODUCT DOMESTICT BRUTO (PDRB) PROVINSI DKI JAKARTA - Jimmy Roland Alfius Torar (AkMen JURNAL ILMIAH, 2018)
The purpose of this research is to measure effect of The Urgent Rehabilitation Project in Tanjung Priok against Gross Domestic Product Regional (PDRB) at DKI Jakarta. Data collection in this study used a survey method, population in this research is project data from The Urgent Rehabilitation within 12 years from 2004 – 2015 and all populations are sampled. Multiple linear regression used as analytical method with SPSS software assist. The result of research show that quantity of goods and passengershave significant effect on the acquisition of the amount of the Gross Domestic Product Regional (PDRB) of DKI Jakarta Province contributed by the Sea Transportation Sector.